67.8k views
3 votes
CJ = 2x – 1 and
JT = 82 – 43

CJ = 2x – 1 and JT = 82 – 43-example-1
User Aaron Cook
by
4.8k points

2 Answers

5 votes

Answer:

CT = 10x-44

Explanation:

Since J is the midpoint you would set your equation up like this

  • 2x-1+8x-43

Now you would add like terms

  • 10x-44

Hope this helps!

User Ladan
by
5.0k points
7 votes

The length of CT is 39 .

Since J is the midpoint of CT, we know that CJ = JT.

Therefore, we can set the two expressions for CJ and JT equal to each other and solve for x:

2x - 1 = 82 - 43

2x = 40

x = 20

Now that we know x = 20, we can plug it back into either expression for CJ or JT to find the length of CT.

Let's plug it into the expression for CJ:

CJ = 2(20) - 1

CJ = 39

Therefore, the length of CT is 39.

Solution:

Since J is the midpoint of CT, we know that CJ = JT.

Therefore, we can set the two expressions for CJ and JT equal to each other and solve for x:

2x - 1 = 82 - 43

2x = 40

x = 20

Now that we know x = 20, we can plug it back into either expression for CJ or JT to find the length of CT.

Let's plug it into the expression for CJ:

CJ = 2(20) - 1

CJ = 39

User Imoum
by
5.4k points